решить пример

решить пример

  • frac{3^{3x}+3^{2x}-12*3^{x}}{3^{x}(3^{x}-3)}

    t=3^{x}

    frac{t^{2}+t^{2}-12*t^{2}}{t*(t-3)}

    frac{t^{2}+t-12}{t-3}

    frac{(t-3)*(t+4)}{t-3}

    3^{x}+4

    Ответ:3^{x}+4

  • frac{27^{x}+9^{x}-12cdot3^{x}}{3^{x}(3^{x}-3)}=frac{3^{x}(9^{x}+3^{x}-12)}{3^{x}(3^{x}-3)}=frac{9^{x}+3^{x}-12}{3^{x}-3}=frac{9^{x}-9+3^{x}-3}{3^{x}-3}

    frac{9^{x}-9+3^{x}-3}{3^{x}-3}=frac{(3^{x}-3)(3^{x}+3)-(3^{x}-3)}{3^{x}-3}=frac{(3^{x}-3)(3^{x}+3+1)}{3^{x}-3}=3^{x}+4